Bank Reserves and Financial Stability - SIEGEL, JEREMY J. (Journal of Finance, 1981)
ABSTRACT A stochastic financial model is developed which derives the reserve levels on financial assets which minimize price level fluctuations. It is shown that these levels of reserves are a function of the structure of unanticipated shocks to asset demands and are, in general, quite different from the levels which minimize the fluctuations of either the nominal or real value of these assets. Application of the model to currency and demand deposits in the U.S.A. suggest that the price‐Stablizing reserve ratio on demand deposits is approximately one‐half of the 12% currently mandated by the Monetary Control Act of 1980.